Evidence of association between SNAP25 gene and attention deficit hyperactivity disorder in a Latin American sample (2014)
Attention deficit hyperactivity disorder (ADHD) is one of the most highly heritable behavioral disorders in childhood, with heritability estimates between 60 and 90 %. Family, twin and adoption studies have indicated a strong genetic component in the susceptibility to ADHD. The synaptosomal-associated protein of molecular weight 25 kDa (SNAP25) is a plasma membrane protein known to be involved in synaptic and neural plasticity. Animal model studies have shown that SNAP25 gene is responsible for hyperkinetic behavior in the coloboma mouse. In recent studies, several authors reported an association between SNAP25 and ADHD. In this study, we used a case-control approach to analyze the possible association of two polymorphisms of SNAP25 for possible association with ADHD in a sample of 73 cases and 152 controls in a Colombian children population. Polymorphisms are located in 3? untranslated region of SNAP25, positions T1065G and T1069C. We found a significant association with the GT haplotype (rs3746554pipers1051312) of SNAP25 (p = 0.001). Evidence of association was also found for the G/G genotype of rs3746554 (p = 0.002) and C/C genotype of rs1051312 (p = 0.009). This is the first study in a Latin American population. Similar to other studies, we found evidence of the association of SNAP25 and ADHD. © 2013 Springer-Verlag Wien.